Driver Anti-Sleep Alarming and Protection - Alok Kumar; Shailesh Gautam (International Journal of Electronics Automation, 2026)
Road​‍​‌‍​‍‌​‍​‌‍​‍‌ accidents due to driver drowsiness is one of the biggest problems worldwide, which kills thousands of people every year. Fatigue slows the reaction time, reduces the concentration, and, most importantly, impairs the judgment, thus making drowsy driving as dangerous as drunk driving. To reduce such accidents, various technologies have been employed to develop driver anti-sleep devices. These include sensor-based detection, camera-based eye monitoring, EEG analysis, and real-time alert systems. The concept, design, and operation of these gadgets are examined in this study, along with their various kinds, essential parts, benefits, and drawbacks. In order to prevent accidents, it describes how these systems continuously monitor driver behavior, identify early signs of drowsiness, and deliver timely alerts via alarms, vibrations, or notifications. The study also emphasizes how intelligent cars, Internet of Things (IoT) integration, and AI-based fatigue detection models are becoming increasingly important for improving traffic safety. Understanding how this cutting-edge technology can successfully lower accident rates and guarantee safer driving conditions for people and society as a whole is the main goal. This study explores the concept, design, working principles, types, components, advantages, limitations, and future scope of driver anti-sleep devices. The objective of the study is to learn how these systems detect drowsiness, give alerts, and thus prevent road accidents. The paper also emphasizes the use of intelligent vehicles, IoT integration, and AI-based fatigue detection models for the safety of the ​‍​‌‍​‍‌​‍​‌‍​‍‌driver.
Keywords: Anti-Sleep Device; Driver Drowsiness Detection; Fatigue Monitoring; Road Safety Technology; accident prevention